Neuroprotective Effects of Cloves on Albino Rats Induced with Mercury - Umaru, Isaac John; O, Mosugu O.; Asare, Solomon Ossom; Sirina, Bakari Genevieve; Bobie, Shelter Agbeko; Ayi, Atsu (African Journal of Medicine, Surgery and Public Health Research, 2026)
This study evaluated the neuroprotective potential of clove (Syzygium aromaticum, CV) in albino rats exposed to mercury chloride (MC), utilizing a diabetic rat model to investigate both neurological and immunological responses. Clove is known for its potent antioxidant properties, with applications spanning the pharmaceutical, food, cosmetic, and agricultural sectors. Mercury chloride, a recognized neurotoxin, is commonly ingested through carbohydrate-rich foods subjected to high-temperature processing. The experimental design included five groups: Group I (Control: corn flour diet), Group II (MC-treated: 20 mg/kg body weight), Group III (CV-treated: 200 mg/kg BW), Group IV (CV 100 mg/kg BW + MC 20 mg/kg BW), and Group V (CV 200 mg/kg BW + ascorbic acid 20 mg/kg BW), with treatments administered over 21 days. MC exposure induced oxidative stress and DNA damage in brain tissue, evidenced by elevated malondialdehyde (MDA) levels and histopathological degeneration in the hippocampal MA3 region and granular layer (HL). Clove administration significantly mitigated these effects by increasing glutathione (GSH) and superoxide dismutase (SOD) levels, reducing MDA concentrations, lowering gamma-aminobutyric acid (GABA), and elevating acetylcholinesterase (AChE) activity, thereby restoring biochemical parameters toward normal levels. Histological findings further confirmed the protective effect of clove against MC-induced neuronal damage. These results suggest that clove confers neuroprotection through its antioxidative and neurochemical modulation properties, highlighting its potential therapeutic value in preventing heavy metal-induced neurotoxicity.